Fungsi dan Makna Mantunu Tedong dalam Upacara Rambu Solo’ pada Masyarakat Desa Salu Baruppu’, Toraja Utara - Petrus, Riswan; Kumbara, A.A.N. Anom; Aliffiati, . (Sunari Penjor : Jurnal of Anthropology, 2024)
The Toraja people have a death ceremony which is usually called the rambu solo’. In carrying out the rambu solo’ ceremony, there is a process of buffalo sacrifice which is commonly called mantunu tedong. But now mantunu tedong have changed its meaning where formerly the tedong/buffalo that was sacrificed would be used as a vehicle and provision for the deceased to get to the spirit realm but now its become a place to show off wealth. This study aims to determine the function and meaning of mantunu tedong in rambu solo’ ceremony for the people of Salu Baruppu Village, North Toraja. This study uses qualitative methods, using interpretive theory and religious functions. Mantunu tedong for the people of Salu Baruppu Village, North Toraja has several functions, namely as a symbol of wealth and one's position in society and as a benchmark in carrying out the rambu solo’ ceremony, as well as strengthening kinship relations in society. Mantunu tedong is interpreted as a form of gratitude and final respect for those who have died.